Measuring Patient Safety: The Medicare Patient Safety Monitoring System (Past, Present, and Future). Issue 3 (21st April 2021) - Classen, David C.; Munier, William; Verzier, Nancy; Eldridge, Noel; Hunt, David; Metersky, Mark; Richards, Chesley; Wang, Yun; Brady, P. Jeffrey; Helwig, Amy; Battles, James
Abstract: The explicit declaration in the landmark 1999 Institute of Medicine report "To Err Is Human" that, in the United States, 44, 000 to 98, 000 patients die each year as a consequence of "medical errors" gave widespread validation to the magnitude of the patient safety problem and catalyzed a number of U.S. federal government programs to measure and improve the safety of the national healthcare system. After more than 10 years, one of those federal programs, the Medicare Patient Safety Monitoring System (MPSMS), has reached a level of maturity and stability that has made it useful for the consistent measurement of the safety of inpatient care. The MPSMS is a chart review–based national patient safety surveillance system that provides rates of 21 specific hospital inpatient adverse event measures, which have been divided into 4 clinical domains (general, hospital-acquired infections, postprocedure adverse events, and adverse drug events) for analysis. The 2014 MPSMS national sample was drawn from 1109 hospitals and includes approximately 20, 000 medical records of patients admitted to the hospital (all payors) for at least 1 of the 4 conditions of congestive heart failure, acute myocardial infarction, pneumonia, and major surgical procedures as defined by the Centers for Medicare and Medicaid Services Surgical Care Improvement Project. The MPSMS is now going through a major transformation to capture additional types of adverse events and is being redeveloped as the Quality and Safety Review System (QSRS). As an example of this transformation, QSRS will electronically import electronic data, which are standardized according to the Centers for Medicare and Medicaid Services billing definitions and will be updated and evolve over time to incorporate expanded standardized data available from electronic health records. This article reviews the development of MPSMS, the strengths and limitations of MPSMS, and expected future directions in patient safety measurement, focusing on those issues that are informing the development and implementation of QSRS.